SPYING METHOD TO IMPROVE THE ENGLISH SPEAKING SKILL OF THESTUDENTS OF THE EXTRACURRICULAR ENGLISH CONVERSATION CLUBIN SMP N 6 YOGYAKARTA - Ratna Rismayanti; Diah Meta Arofah; Fitri Alfarisy (Pelita - Jurnal Penelitian Mahasiswa UNY, 2013)
The objective of the research was to reveal the interests of the junior highschool students in English and the effectiveness of using the spying method toimprove their interests.The research was a classroom action research. The subjects were the studentsof SMPN 6 Yogyakarta. The reserach was conducted in one cycle consisting ofplanning, acting, and reflecting. To complete the data, the teacher was interviewed.The findings showed that the spying method was an innovative teachingstrategy. It can be seen in the improvement of the students’ skill in the English conversations.Most of the students spoke actively and did not feel afraid and shy though notmaximally yet. This method also helped them learn new vocabularies and pronunciation.Based on the interview with the teacher, it can be concluded that the spyingmethod could help the teacher improve the students’ interest in the English subject.